Assessment of the Potentiality to the Debris-Flow Occurrence from Morphometrics Parameters extracted by Remote Sensing techniques: a Case Study in Santo Antônio Basin (Caraguatatuba, São Paulo State, Brazil) - dos Santos Corrêa, Claudia V. [UNESP]; Reis, Fábio Augusto G.V. [UNESP]; do Carmo Giordano, Lucilia [UNESP]; Cabral, Victor Carvalho [UNESP]; Veloso, Vinicius Queiroz [UNESP] (My University, 2023)
This work aimed to evaluate the potential of Remote Sensing techniques applied to debris-flow process generation from the Santo Antônio hydrographic basin, in the Serra do Mar region of the coast of São Paulo State, Brazil. Hydrographic basin techniques were applied, and morphometric parameters relevant to the triggering of these processes in watersheds were calculated. The sub-basins located in steep sections of the relief, with high slopes, valleys, and channels docked, high drainage densities present higher values in the morphometric parameters, indicating a greater potential for triggering and occurrence of debris-flow processes.